Persistence of Halophylic Methanogens and Oil-Degrading Bacteria in an Offshore Oil-Producing Facility. Issue 4 (21st April 2018) - Okoro, Chuma Conlette; Nwezza, Elebe Emmanuel; Lin, Johnson
ABSTRACT: Microbial communities in a high saline, Tetrakis-Hydroxymethyl Phosphonium Sulfate (THPS) and nitrate-treated Nigerian oil-producing facilities were investigated. Methanogens in produced water samples preferred methanol, while those in pig-run samples (oily wastes from pipelines) preferred H2 /CO2, as substrates to produce methane and stimulate metal corrosion. The results coincide with the dominance of methylotrophic and hydrogenotrophic methanogens in the respective samples. The same microbial populations were also THPS and high salinity tolerant. The nitrate reducers and hydrocarbon degraders were also dominant in the reservoir. A more inclusive and effective mitigation strategy is therefore required to effectively tackle biocide resistant methanogens in biocide treated oilfield.